Semiotic Analysis Found in Selected Christopher Nolan’s Movie Posters - Rizki Audy Pasya; Dwi Rahayu (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to analyze semiotic signs in two of Christopher Nolan’s movie posters; Interstellar and Oppenheimer. The method used in descriptive qualitative using Roland Barthes’ semiotic theory: denotation, connotation and myth. The data of two posters Interstellar (2014) and Oppenheimer (2023) were taken from Cinematerial website which was selected and identified following Barthes’ (1972) theory of semiotics. The findings yield a total of 27 data that consists of; 11 denotations, 11 connotations, and 5 myths. Through analyzing these signs, we can gain insight into the films’ narratives, plot, and the art direction of the movie poster design as a communication tool. It can be concluded that semiotic analysis gives a valuable approach to understanding the deeper meanings of visual media. As such, different individual’s experience or cultural background can develop their own meaning of the posters.